Investigation of heat transfer during melting of a PCM by a U‐shaped heat source. (29th May 2017) - Bashar, Mohammad; Siddiqui, Kamran
Summary: An experimental study was conducted to investigate the melting process of a phase change material (PCM) and the associated convection heat transfer due to a U‐shaped heat source embedded in the PCM. The experiments were conducted at four input heat fluxes that varied from 3450 to 5840 W/m 2 . The results showed that the heat transfer behavior, interface movement, and the heat transfer coefficients differed both axially and vertically inside the chamber. The local convective heat transfer coefficient in the inner region, enclosed by the U‐tube, was found to be about 35% higher than that in the outer region over the input heat flux range, resulting in faster melting in the inner region than in the outer region. As melted domain grew vertically from 15% to 100%, it was observed that the overall h in the inner region increased by 40–55% from the lowest to highest heat flux. The melting rate was also found comparatively high up until 65–70% of the total PCM volume melted because of the higher contribution from the inner region. It was also observed that the Rayleigh number increased by approximately 23% in the inner region and 18% in the whole domain as the heat flux increased from 3450 to 5840 W/m 2 . A new Nusselt–Rayleigh number correlation is proposed for the heat transfer during the melting process due to a U‐shaped heat source. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Investigated the melting process and associated convection heat transfer in a phase change material because of an embedded U‐shaped heat source. The geometry of the heat source significantly influenced the solid‐liquid interface dynamics and local heat transfer coefficient. The heat transfer coefficient in the inner region of the heat source was significantly higher that that in the outer region. A new Nusselt‐Rayleigh numbers correlation is proposed for the heat transfer during the melting process because of a U‐shaped heat source.